DIPLOMASI KOMERSIAL KONSULAT JENDERAL REPUBLIK INDONESIA KUCHING DALAM MENGEMBANGKAN PERDAGANGAN UMKM INDUSTRI PENGOLAHAN INDONESIA DI MALAYSIA PERIODE 2018-2019 - Hesti Rokhaniyah; Novi Rizka Amalia; Ida Susilowati; Bagas Husnul Hidayat (Dauliyah: Journal of Islam and International Affairs, 2022)
This study aims at finding out how the role of the Consulate General of the Republic of Indonesia Kuching in developing the Indonesian Manufacturing MSME in Sarawak Malaysia for the 2018-2019 period. Through various exhibition activities, coordination between the Indonesian and Sarawak governments and the cooperation. The two Indonesian Consulates, commercial diplomacy seeks to develop Indonesian MSME. This study employed a qualitative descriptive method using data collection techniques from books, journals, interviews, and data obtained from government agencies while the data processing techniques utilized reduction, presentation of analysis and drawing conclusions. The results of this study indicated that the role of the Indonesian Consulate General through facilitation, advisory and representation points in commercial diplomacy provided opportunities for Indonesian micro and small businesses in Sarawak through exhibition facilities provided by the Consulate General to promote MSME products on a regular basis in Sarawak. In addition, the exhibition facilities of the Indonesian Consulate General in Kuching accommodate various kinds of information for the benefit of MSME business partners and parties who cooperated in achieving their goals as well as coordinating and collaborating with the Sarawak government for the national interest.